Organizations on the Couch: clinical perspectives on organizational behaviour and change - Kets de Vries, Manfred, and Associates (Jossey-Bas Publishers San FranciscoUS, 1991)
Demonstrates how the psychoanalytic perspective can be applied to analyze and change unhealthy behaviour patterns in organizations. Looks at conceptual frameworks; focusses on leadership and group processes; as well as covers the questions of organizational character, consultation and change.